2008
DOI: 10.1097/mnm.0b013e3282f30461
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of myocardial perfusion abnormalities in patients with varying degree of coronary artery stenosis

Abstract: Patients with CAD risk factors, and coronary arteries with insignificant stenosis on angiography, may demonstrate inducible reversible myocardial ischaemia. This is suggestive of coronary endothelial dysfunction. Patients with insignificant coronary artery stenosis and no previous history of adverse coronary events may demonstrate features of previous myocardial infarction on MPS. The severity of perfusion defects demonstrated by MPS may be independent of the anatomical location of coronary artery stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…They concluded that patients with insignificant stenosis coronary angiography may show inducible myocardial ischemia resulting from coronary endothelial dysfunction. In addition, the severity of perfusion defects proven by MPI may be independent of the anatomical location of coronary artery stenosis (32). Multiple logistic regression analysis revealed that HbA1c concentration, in addition to pretest likelihood of CAD, was also a strong predictor of ischemia.…”
Section: Discussionmentioning
confidence: 95%
“…They concluded that patients with insignificant stenosis coronary angiography may show inducible myocardial ischemia resulting from coronary endothelial dysfunction. In addition, the severity of perfusion defects proven by MPI may be independent of the anatomical location of coronary artery stenosis (32). Multiple logistic regression analysis revealed that HbA1c concentration, in addition to pretest likelihood of CAD, was also a strong predictor of ischemia.…”
Section: Discussionmentioning
confidence: 95%
“…helpful. In the literature, a number of investigations focused on this issue[27][28][29][30][31][32][33][34][35][36] . Alqaisi et al compared the outcomes in 125 patients with abnormal MPI and insignificant CAD with 136 patients as a control group over a 24-month follow-up.…”
mentioning
confidence: 99%
“…Consistent with our data, the prevalence of myocardial perfusion abnormalities in asymptomatic subjects has been reported to be between 20-50% and is attributed to the presence of CAD risk factors and/or family history. [19,45,46] A number of underlying mechanisms have been suggested for ischemia being silent, including subclinical epicardial disease, microvascular dysfunction,[47] blunted pain perception or insufficient degree of ischemia to stimulate pain receptors. Our findings suggest that endothelial dysfunction can play an important pathophysiologic role, independent of traditional CAD risk factors and family background and provides mechanistic insight for the link between FMD and coronary heart disease events.…”
Section: Discussionmentioning
confidence: 99%